A solvent-free epoxy heavy-duty anticorrosive coating for marine engineering and preparation method thereof

Through system thinking and full-process management methods, combined with heavy anti-corrosion, solvent-free, temperature-resistant and heat-insulating technologies, a two-component solvent-free epoxy heavy anti-corrosion coating was designed, which solved the problems of insufficient impact, thermal stress and wear resistance of coatings in marine engineering, and achieved high-performance and long-life coating protection effect.

CN116694191BActive Publication Date: 2025-03-21沈希
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310839099.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2025-03-21
Estimated Expiration
2043-07-10

AI Technical Summary

Technical Problem

Existing solvent-free epoxy heavy corrosion-proof coatings have insufficient impact resistance, thermal stress resistance and wear resistance in marine engineering, resulting in the coating being prone to cracks, cracks and even falling off in dry, wet, cold and hot environments.

Method used

Using system thinking and full-process management methods, combined with cutting-edge technologies such as heavy anti-corrosion, solvent-free, temperature-resistant and heat-insulating, and micro-interface, a two-component solvent-free epoxy heavy anti-corrosion coating was designed. The coating consists of 2602 modified epoxy resin, scale filler, drift beads, corrosion-resistant filler, wear-resistant filler, cross-linkable curable active solvent, additive and temperature-resistant curing agent.

Benefits of technology

It achieves the coating's high permeability, acid and alkali resistance, salt spray resistance, moisture and heat resistance, high temperature resistance, wear resistance, impact resistance and thermal stress resistance, extends the service life of the coating and is suitable for long-term protection of steel structures and concrete structures under various severe corrosion environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to the field of coatings, and in particular to a solvent-free epoxy heavy anticorrosive coating for marine engineering and a preparation method thereof. Component A of the coating consists of epoxy resin E44, 2602 resin, epoxy active solvent, floating beads, wet-ground muscovite flakes, graphite flakes, cast stone powder, titanium dioxide, talcum powder, fumed silica and additives, and can be manufactured at room temperature. Component B is a Mannix addition polyamine curing agent. The product has the characteristics of high performance, economy, environmental friendliness, energy saving and easy construction. A variety of green and low-carbon technologies are used in the manufacturing process to reduce pollution, save resources, reduce costs, and improve social and economic benefits. The coating has strong adhesion to steel and concrete, a dense structure, resistance to freezing and thawing, resistance to dry-wet cold and hot alternation, and good impact resistance and wear resistance. It has outstanding corrosion resistance to seawater, salt spray, acid, alkali, salt, oil, soil, sewage and chemical atmosphere, and is an ideal high-performance anticorrosive material for steel structures and concrete structure engineering including marine engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of heavy-duty anti-corrosion coatings, and specifically relates to a wear-resistant, heat-stress corrosion-resistant solvent-free epoxy heavy-duty anti-corrosion coating and a preparation method thereof, which is suitable for long-term protection of steel structures and concrete structures in various severe corrosion environments including marine engineering. Background Art

[0002] Traditional low-solid solvent-based coatings contain about 50% organic solvents. During the manufacturing, construction, drying, and curing process of the coatings, a large amount of volatile organic compounds (VOCs) are emitted into the atmosphere, causing extremely serious pollution to the ecological environment. As people's environmental awareness increases, environmentally friendly coatings will become a consumer fashion. Researching and developing "environmentally friendly coatings" that meet the requirements of ecology, efficiency, and energy - solvent-free coatings, will have great strategic significance and broad market prospects.

[0003] Solvent-free coating is a new type of high-performance coating, also known as active solvent coating, which refers to a type of high-solid content coating in which the solvent eventually becomes a coating component and does not emit VOC into the atmosphere during the curing process. At present, many well-known coating companies abroad have produced it. Such as Sigma, IP International, Ameron in the United States; London Paint in Norway; Hellman Paint in Denmark; Kansai Paint Company in Japan; SPC in Australia, etc. Solvent-free coating has good anti-corrosion performance, and the solid content can be close to or reach 100%. There is no solvent volatilization during curing, which meets environmental protection requirements; the coating has a small shrinkage rate, no pinholes, and good anti-seepage performance, which not only eliminates the risk of poisoning and fire, but also is suitable for relatively closed cabins and indoor construction. It can also reduce ventilation equipment, avoid resource waste and environmental pollution caused by solvent volatilization, and ensure the safety of ecology and staff; solvent-free coating is a thick coating, and the thickness of each coating can reach more than 200µm, or even 700µm; the coating has high bonding strength and small shrinkage rate, which reduces the number of construction passes. Traditional solvent-based coatings lose up to 50% of their volume fraction after the solvent evaporates, while solvent-free coatings do not cause loss of coating quality, can be applied thickly, and have high construction efficiency. Therefore, the total cost of use is low, which can generate very considerable economic and environmental benefits.

[0004] Heavy-duty coating is relative to conventional anti-corrosion coating. Its English translation is: Heavy-Duty Coating. It is a type of anti-corrosion coating that can be used in a very harsh corrosive environment and can achieve a longer protection period than conventional anti-corrosion coatings. Heavy-duty coatings are generally required to have a protection period of more than 5 years in acid, alkali, salt and solvent media, and generally more than 10 to 15 years in chemical atmosphere and marine environment. The application of heavy-duty coatings involves various fields of modernization, large industrial and mining enterprises: pipelines, storage tanks, equipment, etc. in chemical, petrochemical, steel and large-scale mining and smelting; important energy industries: natural gas, oil pipelines, oil tanks, power transmission and transformation, nuclear power equipment and coal mines; modern transportation: bridges, ships, containers, trains and cars; emerging marine engineering: offshore facilities, coastal and bay structures and offshore oil drilling platforms.

[0005] The coastal areas have developed economies and concentrated industries, and a large number of steel and reinforced concrete facilities have been built, such as bridges, docks, piers, pipelines, storage tanks, power stations, etc. Due to the influence of the marine environment, the corrosion problem is quite prominent. Strengthening the research and application of corrosion protection technology is of great value to ensure the safe service of coastal engineering structures. Corrosion protection is an important issue that must be solved in marine development and coastal economic development, and it is of great value to my country's economic development. Among the methods of metal and concrete corrosion protection, organic coatings are the most widely used protective layers. One important reason is that when the protective layer is damaged, it is relatively convenient to repeatedly reapply or replace the coating. Solvent-free heavy-duty anti-corrosion coatings have achieved rapid development due to their many excellent properties.

[0006] Seawater is a relatively complex corrosive environment, which contains a variety of inorganic salts, organic matter, dissolved gases, suspended matter, colloids, organisms, etc. In particular, seawater contains high concentrations of salt (such as sodium chloride, etc.), a large number of marine organisms (macro-organisms and microorganisms), a certain concentration of oxygen, etc., and the chloride ions in it are highly corrosive. Coupled with the fouling of marine organisms, the corrosion resistance of metal materials such as steel in the marine environment is very serious. At the same time, pH value, oxygen content, pollutants, sea wave splashing, sunlight exposure, day and night temperature and humidity alternation, etc. are also important factors that accelerate marine corrosion. Among them, the splash zone and tidal range zone are the most severely corroded due to the high oxygen content caused by the alternation of dry and wet. The selected anti-corrosion coating should be able to adapt to the alternation of dry and wet, and have stringent requirements for wear resistance, impact resistance, and good weather resistance.

[0007] In order to achieve the purpose of bearing loads, marine engineering structures are mainly made of metal materials, followed by reinforced concrete structures. In the long-term service process, metal materials will inevitably corrode. Coating protection is the most widely used key technology in marine anti-corrosion. There are many types of coatings, and the anti-corrosion life varies greatly. It is necessary to select the type and thickness of the coating according to the anti-corrosion life requirements of different areas (atmospheric area, wave splash area, tidal range area, full immersion area, and sea mud area). Marine steel structure anti-corrosion coatings need to have high adhesion to steel substrates, resistance to chloride ion corrosion penetration, resistance to salt spray, resistance to moisture and heat, resistance to strong ultraviolet rays, resistance to seawater erosion corrosion, good compatibility with electrochemical protection systems, and good construction performance. Marine concrete anti-corrosion coatings should have the characteristics of resistance to seawater erosion, salt spray, alkali resistance, high toughness, high adhesion, and wear resistance. Among them, solvent-free epoxy heavy anti-corrosion coatings have become the most economical, important, and widely used protective coatings in marine environments due to their excellent adhesion, corrosion resistance, matching, and thick coating properties.

[0008] Solvent-free epoxy heavy-duty anti-corrosion coatings are generally two-component coatings composed of epoxy resin, toughening resin, flake filler, active solvent and modified amine curing agent. Because the coating does not contain volatile organic solvents, the solid content is close to 100%. After curing, a pinhole-free coating is formed, which has excellent corrosion resistance, chemical resistance and electrical insulation. This kind of coating has strong adhesion and dense structure. It has outstanding anti-corrosion performance against seawater, acid, alkali, salt, soil, crude oil, gasoline and chemical atmosphere. It is an ideal corrosion-resistant material for today's large steel and concrete structure projects.

[0009] There are reports on the related technologies of solvent-free epoxy heavy anti-corrosion coating and preparation method, such as the patent with publication number CN113025165A, the patent with the name of "a solvent-free epoxy heavy anti-corrosion coating and its preparation method and application", the patent with publication number CN109321126A, the patent with the name of "a solvent-free heavy anti-corrosion coating and its preparation method", the patent with publication number CN109082198A, the patent with the name of "solvent-free environmentally friendly heavy anti-corrosion coating for marine steel structure", the patent with publication number CN10997130 6A, patent named "Solvent-free heavy-duty anti-corrosion coatings, anti-corrosion coatings and marine structures", patent publication number CN104530921A, patent named "A method for preparing tough epoxy heavy-duty anti-corrosion coatings"; related publications such as "Li Guilin, High Solids Coatings [M], Beijing: Chemical Industry Press: P.373-463", "Sun Manling, ed., Principles and Technology of Epoxy Resin Application [M], Beijing: Machinery Industry Press, P.331-337", etc. have detailed introductions.

[0010] At present, the application of solvent-free epoxy heavy-duty anti-corrosion coatings in marine engineering protection still has the following problems:

[0011] (1) Some products also need to be equipped with epoxy zinc-rich primer, which cannot achieve the integration of primer and topcoat. The coating structure is too complicated, making construction management more difficult.

[0012] (2) Some products still cannot be coated thickly, which increases the number of construction passes and costs required to achieve the designed coating thickness.

[0013] (3) The coating’s ability to resist thermal stress corrosion is insufficient, and it is prone to cracks, splitting, or even falling off in dry or wet, or rapid cooling or heating environments.

[0014] (4) The wear resistance of the coating is not strong enough to meet the wear resistance requirements in ocean splash zones and tidal range zones.

[0015] (5) The coating is very brittle and lacks toughness. It is prone to cracking and falling off when exposed to the harsh environment of waves and floating objects for a long time.

[0016] The purpose of the present invention is to develop a "solvent-free epoxy heavy-duty anti-corrosion coating" that can be used in severe corrosive environments including marine engineering, and to achieve "primer and topcoat in one" and thick coating in engineering.

[0017] It can be seen from the failure cases and use environment of anti-corrosion coatings that the coating is in a harsh environment of high and low temperature alternation, high humidity and heat, high wear and various corrosive media for a long time during use, and the performance requirements of the product are extremely stringent. The overall technical requirements for coatings and coatings are as follows:

[0018] 1) Strong impermeability, low water absorption, good insulation, and resistance to long-term erosion by corrosive media such as acid, alkali, salt, oil, seawater, salt spray, damp heat, and microorganisms;

[0019] 2) Good wear resistance;

[0020] 3) Small shrinkage during curing and small thermal expansion coefficient;

[0021] 4) The coating has good flexibility and strong impact resistance;

[0022] 5) It has high thermophysical and thermochemical stability and can withstand temperatures above 160°C for a long time;

[0023] 6) The coating has good adhesion to steel and concrete, and the main structure has high strength;

[0024] 7) Good resistance to sudden changes in humidity, temperature and humidity (-20℃~100℃);

[0025] 8) The solid content of the coating is ≥98%;

[0026] 9) "Base and topcoat in one", can be applied thickly;

[0027] 10) Good construction process and good repairability. Summary of the invention

[0028] In view of the shortcomings of the prior art and the overall technical requirements of anti-corrosion coatings, the present invention provides a green and low-carbon solvent-free epoxy heavy-duty anti-corrosion coating and a preparation method thereof that can be used in severely corrosive environments such as marine engineering.

[0029] The present invention incorporates scientific research methods such as system thinking and whole-process management into the formation and implementation of the overall invention concept and technical solution, and implements the basic principles of "integrity", "comprehensiveness" and "optimization" of system design throughout. One of the differences from the prior art is that it starts from solving the root of the problem, and includes the identification and analysis of the causes and mechanisms of failure of previous coatings during use in the formation of the "technical solution". The second difference is that the "5E" principles and other requirements of the international coatings industry development, such as high performance, economy, environmental friendliness, energy saving, and easy construction, are converted into technical indicators of the invention, and are included in the "technical solution" as "design input". The third difference is that the cutting-edge technologies of functional coatings such as heavy anti-corrosion, solvent-free, thermal insulation, micro-interface, "primer and topcoat in one", and thick coating are effectively integrated into the "technical solution" of the present invention, and produce the beneficial effect that each technical feature supports and enhances each other in function. The detailed technical solution of the present invention is as follows:

[0030] A solvent-free epoxy heavy-duty anti-corrosion coating can be used for anti-corrosion in highly corrosive environments, such as steel structures and concrete structures in severely corrosive environments, and the coating comprises component A and component B;

[0031] The component A is composed of the following raw materials, calculated by weight: based on 100 parts of epoxy resin E44, additionally: 20-25 parts of 2602 resin, 40-46 parts of epoxy active solvent, 14-43 parts of wet-ground muscovite flakes, 10-25 parts of graphite flakes, 6-25 parts of floating beads, 8-12 parts of cast stone powder, 5-8 parts of titanium dioxide, 1-4 parts of talc, 1.5-4 parts of fumed silica, 0.5 parts of coupling agent, 0.5 parts of dispersant, and 0.25 parts of defoaming agent.

[0032] The B component is a Mannich addition polyamine curing agent.

[0033] The weight ratio of the component A to the component B is 7:1 to 5:1.

[0034] The 2602 resin is xylene formaldehyde resin.

[0035] The epoxy active solvent is one or a mixture of propylene oxide butyl ether, C12-14 alkyl glycidyl ether and ethylene glycol diglycidyl ether.

[0036] The wet-ground muscovite flakes have a diameter of 120 to 200 mesh. Preferably, the wet-ground muscovite powder has a diameter of 200 mesh, 160 mesh, 120 mesh, or a mixture of several of them. The quality index should meet the requirements specified in the industry standard JC / T596-2017 "Wet-ground mica powder".

[0037] The quality index of the graphite flakes should meet the requirements of GB / T3518-2008 "Flake Graphite". The flake diameter is preferably 80-200 mesh, for example, one or a mixture of 80 mesh, 100 mesh, and 200 mesh.

[0038] The average particle size of the floating beads is preferably 60-100 meshes, for example, 60 meshes, 80 meshes or 100 meshes, and the floating rate should be ≥ 90%. One or a mixture of floating beads of different specifications can be selected.

[0039] The quality index of the cast stone powder should meet the requirements of JC514.3-93 "Cast stone powder for cast stone products". The average particle size of the cast stone powder is preferably 100-200 mesh, for example, the specifications are 100 mesh, 160 mesh, 200 mesh or a mixture of several thereof.

[0040] The titanium dioxide is rutile titanium dioxide, and its quality index meets the requirements of GB / T1706-2006 "Titanium Dioxide Pigment" standard.

[0041] The quality requirements of the talcum powder should comply with the requirements of GB / T15342-2012 "Talc", and the fineness should be ≤325 mesh.

[0042] The fumed silica should comply with the standard requirements of GB / T20020-2013 "Fumed Silica".

[0043] The coupling agent is preferably a silane coupling agent, with the brand name KH-560.

[0044] The defoamer is preferably BYK-A530 produced by BYK of Germany.

[0045] The dispersant is preferably EFKA-5054 produced by Efka.

[0046] The present invention adopts a systematic thinking method. In the overall inventive concept, it widely absorbs the cutting-edge technologies such as heavy-duty anti-corrosion, solvent-free, heat-resistant and heat-insulating, micro-interface, green and low-carbon in the development of industrial coatings, and integrates them into the formulation design of the coating. On the premise of meeting other technical performance indicators of solvent-free heavy-duty anti-corrosion coatings, it focuses on solving the three key technical problems of "marine engineering solvent-free heavy-duty anti-corrosion coatings" and coatings, such as insufficient impact resistance, thermal stress resistance and wear resistance.

[0047] The design principle of the present invention and the role of each raw material in the formula are as follows:

[0048] (1) Resin

[0049] Bisphenol A epoxy resin is soluble in a variety of solvents. The resin has good processability and can form excellent performance solids with a variety of curing agents to meet various usage requirements. The solid has high body strength and bonding strength, high corrosion resistance and electrical properties, and certain heat resistance. The main disadvantages are: greater brittleness, poor moisture and heat resistance and weather resistance. The resin grade commonly used in solvent-free epoxy coatings is E51. We use E44 epoxy resin with a larger molecular weight and better flexibility.

[0050] Since low-viscosity epoxy resin cured products are brittle, the flexibility and thermal shock resistance of the coating are poor. For this reason, a part called a toughener is often added to the resin-curing system. The toughener can not only improve the impact strength and thermal shock resistance of the cured product, but also improve the peel strength of the coating, reduce the reaction heat and shrinkage during curing. Its function is to replace the interaction between the epoxy resin molecular segments with the interaction between the toughener molecules and the epoxy resin molecules, so as to reduce the glass transition temperature of the coating, thereby increasing the toughness of the polymer compound and improving the brittleness of the coating.

[0051] The raw materials used for toughening epoxy resins are mainly: polyamide resin, polysulfide rubber, epoxidized polybutadiene resin, nitrile rubber and unsaturated polyester resin. 2602 resin, also known as xylene formaldehyde resin (trade name "Nikanol" resin of Mitsubishi Gas Company of Japan), is a light yellow, transparent, water-like low molecular polymer obtained by the reaction of meta-xylene and formaldehyde in the presence of a catalyst. The CAS number is 26139-75-3. The molecular structure contains active groups such as hydroxyl, ether, methoxy and acetal groups. It has good compatibility with synthetic resins such as epoxy resin. Adding this resin to solvent-free epoxy coatings can not only improve the brittleness and bonding properties of the coating, improve the impact resistance, but also will not reduce the corrosion resistance of the paint film.

[0052] (2) Epoxy reactive solvent

[0053] The solvent used in solvent-free coatings has active groups that can react chemically with the curing agent, so after curing, the solvent will eventually become part of the coating. It is a high-solid content coating that does not emit VOCs into the atmosphere during the curing process. Solvent-free coatings save resources and meet the control requirements of environmental regulations on volatile organic matter (VOC). A single-layer construction can obtain a thick coating, shorten the construction period, reduce the risk of fire, and effectively protect the health of construction workers.

[0054] The principles for selecting epoxy active solvents are: strong ability to dilute resins, non-toxic, no special odor, not easy to volatilize, and able to meet the performance requirements of the paint film. Butanol, isooctyl alcohol, cresol, alkyl alcohols and glycidyl ethers of higher monohydric alcohols and glycidyl esters of fatty acids are commonly used monofunctional epoxy active solvents, and diglycidyl ethers and ethylene glycol diglycidyl ether are commonly used difunctional epoxy active solvents. Among them, propylene oxide butyl ether and C12-14 alkyl glycidyl ether are the most commonly used epoxy active solvents, which have strong dilution ability and are relatively cheap.

[0055] The introduction of monofunctional epoxy active solvents may reduce the crosslinking density of the resin, thereby reducing the heat resistance, impact strength, hardness, and bending resistance of the paint film. In order to take into account the various properties of the coating, while adding a certain amount of monofunctional epoxy active solvents, difunctional epoxy active solvents such as ethylene glycol diglycidyl ether are also used, which have little effect on the thermal deformation temperature of the curing system and have a significant improvement on the flexibility and impact resistance of the paint film. The epoxy active solvents thus compounded not only effectively reduce the viscosity of the resin, but also effectively improve the impact and bending resistance of the paint film.

[0056] (3) Scales

[0057] For heat stress resistant heavy-duty anti-corrosion coatings, in addition to considering corrosion resistance, the selection of fillers should also consider its effect on stress. Flake fillers are commonly used in heavy-duty anti-corrosion coatings because flake fillers can block the passage of corrosion factors such as water, oxygen, and ions, and cut off the capillaries in the paint film. Parallel and overlapping flakes can play a maze effect in the paint film, prolong the path for corrosion factors to penetrate into the paint film, and improve the anti-corrosion ability of the coating. At the same time, in the flake coating, the resin is divided into small scattered areas by the flakes, so that the shrinkage stress generated by curing or the thermal stress generated by the ambient temperature offsets each other in the reduced area and relaxes without transmission and superposition. In this way, the residual stress in the coating will be greatly reduced, and the possibility of microcracks caused by thermal stress will also be greatly reduced. Therefore, flake fillers play a key role in greatly improving the corrosion resistance of heavy-duty anti-corrosion coatings and reducing the risk of thermal stress corrosion.

[0058] Wet-ground muscovite flakes are widely available, cheap, and have excellent insulation, elasticity, and toughness. They have a large diameter-to-thickness ratio, a small thermal expansion coefficient, are completely inert in various chemical corrosive media such as hydrofluoric acid, and have outstanding anti-permeability properties. Wet-ground muscovite flakes have a reinforcing effect on the coating, which can improve its toughness and spreadability, and prevent corrosion failure such as cracking of the coating. Graphite flakes have good high temperature resistance, wear resistance, electrical conductivity, thermal conductivity, lubrication, plasticity, and impermeability, good chemical stability, and do not react with corrosive media such as hydrofluoric acid. They are one of the most inert materials. Graphite flakes have a layered crystal structure with very small shear strength inside. They are prone to interlayer slippage under the action of external forces, and thus have a friction-reducing and wear-resistant effect. When it is added to the coating, it can effectively reduce the friction coefficient of the coating and extend its wear life. It is an ideal solid lubricating filler to solve the key technical problem of wear resistance in marine environments. By adding a certain amount of wet-ground muscovite flakes and graphite flakes, not only the wear resistance of the coating can be improved, but also the flexibility, impermeability, corrosion resistance and thermal stress corrosion resistance of the coating can be increased.

[0059] (4) Floating beads

[0060] Hollow microspheres are widely used in thermal insulation coatings. Floating microspheres are a type of hollow microspheres. They are hollow thin-walled beads with a diameter of several microns to hundreds of microns. A certain amount of gas is encapsulated inside the sphere. The shape is smooth and round, isotropic, has no sharp edges and corners, and has good dispersion in the resin. Compared with fillers of other shapes, this type of microsphere has the smallest specific surface area, which means that the filling amount of the coating can be increased, while the coating still has good construction performance, which makes it possible to manufacture solvent-free coatings with high solid content. Due to its small expansion coefficient and isotropy, it can effectively reduce the shrinkage of the coating and prevent stress cracking. During the heat transfer process, when encountering hollow microspheres, only a small part of the heat is conducted through the microspheres, while most of the heat bypasses the microspheres, making the heat transfer path longer and causing the heat transfer to decrease. Therefore, the hollow structure of the microspheres can effectively reduce the speed and intensity of radiation heat transfer and thermal conduction heat transfer, and play a role in isolating heat. Thereby reducing the thermal conductivity of the coating, the thermal stress at the interface between the coating and the steel or concrete substrate, and the risk of thermal stress corrosion failure caused by it. In addition, the floating beads also have the advantages of high thermal stability and chemical stability, low oil absorption, light weight, wear resistance, insulation, flame retardancy, non-toxicity, good fluidity, and controllable particle size. In recent years, floating beads as thermal insulation fillers have become a hot topic in the research of lightweight, thin-layer, and high-efficiency thermal insulation coatings. Adding a certain amount of floating beads to the formula can effectively increase the solid content and reduce the cost of the coating, improve the coating's heat resistance, thermal insulation, shrinkage and other properties, and alleviate the thermal stress impact of rapid cooling and heating, high and low temperature alternation on the interface between the coating and the steel substrate. It plays an important role in preventing thermal stress corrosion failures such as cracking of the coating.

[0061] In addition, fly ash is an inorganic residue produced during the combustion of coal-fired boilers, while floating beads are hollow microspheres extracted from fly ash. The development and utilization of floating beads in heavy-duty anti-corrosion coatings not only increases the added value of fly ash utilization and reduces environmental pollution, but also reduces the coating industry's dependence on other functional fillers. It is an ideal resource utilization method.

[0062] (5) Filling

[0063] Unlike ordinary paint, it is essential to use fillers in the formulation of corrosion-resistant coatings. This is not only due to cost considerations, but more importantly, fillers can directly affect the corrosion resistance of the paint film. Practice has proved that it is very important to reasonably select fillers and determine the appropriate amount for corrosion-resistant coatings. Commonly used corrosion-resistant fillers include cast stone powder, mica, talcum powder, titanium dioxide, ceramic powder, barium sulfate, silicon dioxide, glass powder, asbestos powder, etc. The corrosion-resistant fillers selected by the present invention are titanium dioxide, cast stone powder and talcum powder, and the basic properties they possess are as follows:

[0064] Cast stone is a non-metallic corrosion-resistant material made of diabase, basalt or shale, industrial waste, certain additives (amphibolite, dolomite, fluorite, etc.) and crystallizers (chromite powder, etc.), through high-temperature melting, casting, crystallization, annealing and other processes. It is famous for its wear resistance and corrosion resistance. It is almost insoluble in all acids and alkalis except hydrofluoric acid and superheated phosphoric acid. After reacting with acids and alkalis, it can gradually form a layer of aluminum silicate protective film on the surface, thereby preventing corrosion from chemical media. The biggest feature of cast stone is that it has wear resistance that general materials do not have. The wear resistance coefficient is 0.09~0.14g / cm², which is 5~10 times higher than manganese steel; the Mohs hardness is as high as 7~8, second only to diamond and corundum. Cast stone powder is made from the scraps of cast stone plates by crushing, screening and grading, and is inexpensive. Adding a certain amount of cast stone powder to the coating can improve the performance indicators of the coating such as wear resistance, corrosion resistance and temperature resistance, and can reduce the cost of the coating. It is very important to improve the wear resistance of marine engineering coatings. The research of the present invention shows that the selection and matching of lubricating filler graphite flakes and hard particle filler cast stone powder in this solution is appropriate, and the synergistic effect between them can be used to obtain a wear-resistant coating with excellent performance.

[0065] Titanium dioxide is considered to be the best white pigment in the world and is widely used in the coating industry. It has the characteristics of strong corrosion resistance, high hiding power, strong tinting power, low dosage, easy dispersion, etc. It can increase the mechanical strength and adhesion of the coating, prevent cracks, prevent ultraviolet rays and water penetration, and thus extend the life of the coating. When used together with graphite flakes, different colors of coatings can be prepared, ranging from light gray, medium gray to dark gray.

[0066] The main component of talcum powder is magnesium silicate, which has lubricity, fire resistance, acid resistance, insulation and thixotropy. It is a physical filler widely used in coatings, which has a certain improvement effect on preventing the sedimentation of other fillers and the sagging of coatings. It can also absorb certain stretching stress and avoid cracks and gaps in the coating.

[0067] (6) Thixotropic agent

[0068] Solvent-free epoxy heavy anti-corrosion coating is a thick paste coating. Since the coating formed by one application is thick, the sliding of the glue often causes serious sagging of the coating before curing. Therefore, an appropriate amount of thixotropic agent must be added to improve the sedimentation and sagging of the coating. Commonly used thixotropic agents include hydrogenated castor oil, aluminum stearate, zinc stearate, organic bentonite and fumed silica. The amount of thixotropic agent added must be just right, so that it can be properly leveled at low viscosity, but the flow time is not too long to avoid sagging. The amount is generally 2%~3% of the total amount of the coating. Through experiments, we added a certain amount of fumed silica to the formula to improve the thixotropic properties of the coating.

[0069] (7) Coupling agent

[0070] In the formula designed by the present invention, fillers such as wet-ground muscovite flakes, graphite flakes and hollow microspheres are the key to the corrosion resistance and temperature change resistance of the paint film, but since there is weak bonding between them and the resin, corrosion factors may penetrate and migrate on the interface. Using a coupling agent to modify the surface of the filler is the most important method to enhance the bonding strength between the base material and the filler, and has a significant effect on improving the mechanical properties and cold-heat alternation resistance of the coating.

[0071] A coupling agent is a compound with two types of active groups, one of which is an inorganic-philic group that can react chemically with the surface of inorganic substances to form chemical bonds; the other is an organic-philic group that forms chemical bonds through addition or polymerization reactions with the active groups in the resin. The commonly used coupling agent for epoxy coatings is silane coupling agent, preferably epoxy or amino type. Studies have shown that after the filler used in the formula is treated with coupling agents such as KH560, its surface will change from inorganic-philic to organic-philic, and the bonding performance with the resin will be greatly improved, thereby improving the mechanical strength, impermeability, corrosion resistance and resistance to cold and hot alternating stress corrosion of the coating.

[0072] (8) Defoaming agent

[0073] High-speed mixing equipment used in the coating production process increases the free energy of the coating during the stirring process, which easily generates foam. If these bubbles remain in the coating after painting, they will affect the corrosion resistance of the paint film. Therefore, defoamers with anti-foaming and defoaming functions are essential for the manufacture of heavy-duty anti-corrosion coatings. BYK-30 can be used in solvent-based and solvent-free coating systems, especially for high-build solvent-free epoxy systems.

[0074] (9) Dispersant

[0075] The dispersion of solid fillers is an important part of coating manufacturing technology. The working principle of dispersants is to adsorb on the surface of fillers to generate charge repulsion, prevent fillers from flocculating, and keep the coating in a stable state. The main component of EFKA-5054 dispersant is a polymer carboxylate, which can reduce the interfacial tension between fillers and resins, improve the storage stability of coatings and the sagging performance of coatings during construction.

[0076] (10) Curing agent

[0077] Solvent-free epoxy coating is a two-component coating, which requires the viscosity of the curing agent used to be low, the service life to be long, and the coating after film formation with the coating to have sufficient strength, toughness and density, so that the coating has the performance of long-term resistance to external mechanical wear, chemical corrosion and stress corrosion. Therefore, the curing agent and cross-linking curing effect are one of the keys to determine the performance of the coating. The curing agent used in this coating is a Mannich addition polyamine containing an aromatic ring, which is a practical non-toxic grade chemical, safe to use, and has the activity of rapidly curing epoxy in low temperature and humid environments. It has good dispersibility in the coating, and the cured coating has good gloss, high hardness, good toughness and density, and low shrinkage. The structure contains benzene rings and phenolic skeleton structures, which further increases the thermal deformation temperature of the cured product, thereby ensuring that the coating has high heat resistance and resistance to chemical media.

[0078] The present invention also provides a method for preparing any of the above-mentioned coatings, wherein the method for preparing component A is as follows:

[0079] (1) Add the weighed epoxy active solvent, epoxy resin E44, 2602 resin, dispersant, coupling agent and defoamer into the reaction kettle in sequence, start the high-speed disperser, control the speed to 300-500 rpm, stir for half an hour, and obtain a mixture;

[0080] (2) Adding the floating beads, fumed silica, wet-ground muscovite flakes, graphite flakes, titanium dioxide, cast stone powder and talcum powder to the mixture of (1) in sequence, stirring at 500-800 rpm for 2 hours;

[0081] (3) Taking samples, testing the viscosity, adding an appropriate amount of wet-ground muscovite flakes or epoxy active solvent to adjust the viscosity to the specified value, and obtaining component A;

[0082] Before construction, mix component A and component B evenly according to the proportion.

[0083] The present invention has the following beneficial effects:

[0084] The "marine engineering solvent-free epoxy heavy-duty anti-corrosion coating" of the present invention follows the "five E" principles of the current international coating industry development, namely, high performance, economy, environmental friendliness, energy saving, and easy construction. It is a "green" heavy-duty anti-corrosion coating developed using technologies such as heavy-duty anti-corrosion, solvent-free, heat-resistant and heat-insulating, and microscopic interface. The coating is a two-component solvent-free epoxy heavy-duty anti-corrosion coating composed of 2602 modified epoxy resin, flake filler, floating beads, corrosion-resistant filler, wear-resistant filler, cross-linkable and curable active solvent, additives, and temperature-resistant curing agent. The technology has the following innovative features and positive effects (the technical performance indicators achieved by the coating and the coating are detailed in Table 3):

[0085] (1) Excellence of finish

[0086] The coating has excellent impermeability, with a solid content of ≥98%. It can resist long-term erosion from acid, alkali, salt, oil, sewage, seawater, salt spray, damp heat, abrasion, chemical atmosphere, microorganisms and various organic solvents. It has strong adhesion to metal and concrete, high mechanical strength, small shrinkage, and is tough and wear-resistant. It can be used for long-term protection of steel (stainless steel) structures and concrete structures in various severe corrosive environments such as dry-wet alternation, high and low temperature alternation, strong acid and strong alkali alternation, including marine engineering. After actual application, the service life of the coating has reached more than 15 years, with good durability.

[0087] (2) Economy

[0088] Less consumables per unit area, high construction efficiency, thick coating, saving resources and engineering construction and maintenance costs. Low cost of use and good economic benefits.

[0089] (3) Environmentally friendly

[0090] The volatile organic compounds (VOC) content is extremely low, which is environmentally friendly, beneficial to the health of operators, and improves safety during use. The first use of floating beads in heavy-duty anti-corrosion coatings has a positive role in increasing the added value of fly ash and reducing environmental pollution.

[0091] (4) Energy saving

[0092] The coating component A is mixed and stirred at room temperature, which is energy-saving and environmentally friendly, with high yield and suitable for large-scale production. The coating can be almost 100% cured into a film, avoiding the waste of resources caused by the volatilization of a large amount of organic solvents.

[0093] (5) Ease of application

[0094] Low surface treatment, thick coating, primer, mid-coat and topcoat in one, can be applied by airless spray, brush or roller, good recoating and maintenance. Construction quality is easy to be guaranteed. DETAILED DESCRIPTION

[0095] The technical solution of the present invention is explained, compared and illustrated in detail below in combination with preferred specific embodiments, so that those skilled in the art can better understand and implement the present invention. The materials and equipment used in the case are all conventionally used chemical substances, instruments and machines disclosed in the art.

[0096] Step 1: Preparation of coating component A

[0097] In this embodiment, the weight ratio of coating component A is shown in Table 1:

[0098] Table 1. Ratio of coating component A

[0099]

[0100] The preparation of coating component A is mixed and processed by a variable frequency high-speed disperser at room temperature. The specific process flow is:

[0101] Epoxy active solvent → Epoxy resin E44 → 2602 resin → Additives (EFKA-5054, KH560, BYK-530, etc.) → Floating beads → Fumed silica → Flakes (wet-ground muscovite flakes, graphite flakes) → Pigments and fillers (titanium dioxide, cast stone powder, talcum powder) → Adjust viscosity (add appropriate amount of wet-ground muscovite flakes or epoxy active solvent) → Online testing → Measuring and packaging → Warehousing → Finished product testing → Delivery

[0102] Step 2: Performance testing of paints and coatings

[0103] (1) Preparation of coating samples, coating panels and samples

[0104] Before preparing the paint, component A must be thoroughly stirred, then the ingredients must be prepared according to the proportions shown in Table 2, and components A and B of the paint must be fully mixed before use.

[0105] Table 2, Heavy Anti-corrosion Coating Ratio

[0106]

[0107] (2) In view of the corrosive environment in which the coating is located, and in combination with the relevant standards and requirements for heavy-duty anti-corrosion coatings and coatings, the test items, technical indicators and test standards for solvent-free epoxy heavy-duty anti-corrosion coatings and coatings for marine engineering are formulated as shown in Table 3.

[0108] Table 3. Technical indicators of solvent-free epoxy heavy-duty anticorrosive paints and coatings for marine engineering

[0109]

[0110] The test results show that the performance of the paints and coatings in Implementation Cases 1 to 4 in Table 1 all meet the technical indicators of "Solvent-free epoxy heavy-duty anti-corrosion paints and coatings for marine engineering" specified in Table 3.

[0111] In view of the three key technical issues that "marine engineering solvent-free epoxy heavy-duty anti-corrosion coating" should solve, namely "impact resistance", "thermal stress resistance" and "wear resistance", single performance comparison tests of the coating were carried out respectively, and a brief description is given here.

[0112] 1. Comparison of toughening effect of coatings

[0113] When 2602 in Table 1 is replaced by butyl nitrile (HTBN), the impact resistance index of the obtained coating is ≤3.9J and the flexibility is 2-3mm. This shows that the toughening effect of HTBN in this system is not good. In the present invention, E44 with better toughness is used to replace the conventional E51, and the bifunctional ethylene glycol diglycidyl ether that can both dilute and toughen epoxy resin and the toughening agent 2602 are selected. These three raw materials synergistically solve the technical problem of the impact resistance of the coating (see the test values ​​of items 7 and 8 in Table 3 for the effect).

[0114] 2. Comparison of heat stress resistance

[0115] The coating obtained by replacing the floating beads in Table 1 with wet-ground muscovite flakes was subjected to a thermal shock test at a temperature of -20℃ to 100℃. After a maximum of three cycles of testing, the coating will produce corrosion phenomena such as cracks. This shows that floating beads have a significant effect on reducing the risk of thermal stress corrosion of the coating (see the test value of item 17 in Table 3 for the effect).

[0116] 3. Comparison of coating wear resistance

[0117] Titanium dioxide was used to replace the graphite flakes and cast stone powder in Table 1, and the coating obtained was tested for wear resistance (1000g, 1000 rpm, weight loss). The weight loss of the coating was at least about 0.05g. The weight loss of the coatings in the table was ≤0.02g. Obviously, the coating obtained by adding graphite flakes with self-lubricating properties and cast stone powder with high wear resistance has significantly improved wear resistance (see the test value of item 11 in Table 3 for the effect).

[0118] Step 3: Project Implementation

[0119] Before coating construction, a corresponding "anti-corrosion plan" should be formulated according to the working conditions of the anti-corrosion engineering device or facility, the warranty period of the coating, and the requirements of the equipment structure. The design thickness of the coating is generally 0.5-2.0 mm. The temperature during construction should be above 0°C and 3°C higher than the dew point. The steel surface should be sandblasted, or treated with tools such as wire brushes, electric brushes, electric grinding wheels or sandpaper, and dust and debris should be removed with a vacuum cleaner, dry and clean compressed air or brushes. Before the coating is prepared, component A should be fully stirred and evenly mixed, and the proportion of component A and component B should be measured according to the required ratio specified in Table 2. The coating should be fully stirred when it is mixed. Brushing, roller coating and high-pressure airless spraying can be used for construction according to specific conditions. After the previous coating is dry, the next coating can be applied until the thickness meets the design requirements. The maintenance period of the coating is generally 5-7 days.

[0120] The "solvent-free epoxy heavy-duty anti-corrosion coating for marine engineering" provided by the present invention has been used on various marine engineering projects, water supply, gas supply, oil supply buried pipelines, sewage treatment facilities, chemical storage tanks, chemical gas holders, towers, platforms, steel frames, water tanks, heavily corroded floors and other steel structures, stainless steel structures and concrete structures. When the coating is inspected during equipment or facility maintenance, the surface is generally intact without shedding or cracking. The coating has a significant anti-corrosion effect and outstanding wear resistance. For defects such as wear and thinning of the coating in a small number of areas, it is only necessary to perform a simple surface grinding treatment on the old coating and apply this product to the corresponding anti-corrosion thickness, so that the original coating can be repaired and continued to be used. At present, the actual service life of many heavy-duty anti-corrosion coatings has reached more than fifteen years.

[0121] Finally, it should be noted that the above is only the basic principle, main features and preferred embodiments of the present invention. It should be clear to those skilled in the art that the present invention is not limited by the above embodiments. Without departing from the design principles and methods of the present invention, modifications and improvements made to the above design scheme should be included in the protection scope of the present invention.

Claims

1. A solvent-free epoxy heavy-duty anticorrosive coating for marine engineering, used in highly corrosive environments, characterized in that: The coating comprises component A and component B; The A component is composed of the following raw materials, by weight: Epoxy resin E44 100 parts, 20-25 parts of 2602 resin, 40-46 parts of epoxy active solvent, 14-43 parts of wet-ground muscovite flakes, 10-25 parts of graphite flakes, 6 to 25 pieces of floating beads, 8-12 parts of cast stone powder, 5-8 parts of titanium dioxide, 1 to 4 parts of talcum powder, 1.5 to 4 parts of fumed silica, 0.25 parts of defoamer, 0.5 parts of dispersant, 0.5 parts of coupling agent; The B component is a Mannich addition polyamine curing agent; The weight ratio of component A to component B is 5 to 7:1; The epoxy active solvent is a mixture of propylene oxide butyl ether, C12-14 alkyl glycidyl ether and ethylene glycol diglycidyl ether.

2. The coating according to claim 1, characterized in that The flake diameter of the wet-ground muscovite mica flakes is 120-200 meshes.

3. The coating according to claim 1, characterized in that The diameter of the graphite flakes is 80 to 200 meshes.

4. The coating according to claim 1, characterized in that The average particle size of the floating beads is 60 to 100 meshes.

5. The coating according to claim 1, characterized in that The average particle size of the cast stone powder is 100-200 meshes.

6. The coating according to claim 1, characterized in that The epoxy resin E44 is a bisphenol A type epoxy resin with an epoxy value of 0.43-0.45 mol / 100g.

7. The coating according to claim 1, characterized in that The titanium dioxide is rutile titanium dioxide.

8. The coating according to claim 1, characterized in that The coupling agent is KH-560.

9. The method for preparing the coating according to any one of claims 1 to 8, characterized in that: The preparation method of component A is as follows: (1) Add the weighed epoxy active solvent, epoxy resin E44, 2602 resin, dispersant, coupling agent and defoamer into the reaction kettle in sequence, start the high-speed disperser, control the speed to 300-500 rpm, stir for half an hour, and obtain a mixture; (2) Adding the floating beads, fumed silica, wet-ground muscovite flakes, graphite flakes, titanium dioxide, cast stone powder and talcum powder to the mixture of (1) in sequence, stirring at 500-800 rpm for 2 hours; (3) Taking samples, testing the viscosity, adding an appropriate amount of wet-ground muscovite flakes or epoxy active solvent to adjust the viscosity to the specified value, and obtaining component A; Before construction, mix component A and component B evenly according to the proportion.

Citation Information

Patent Citations

  • Method for preparing epoxy heavy corrosion-resistant paint with toughness

    CN104530921A

  • Solvent-free heavy anti-corrosion paint and preparation method thereof

    CN109321126A

  • Solvent-free heavy anticorrosive coating, anticorrosive coating and ocean structure

    CN109971306A

  • Solvent-free epoxy heavy anti-corrosion coating as well as preparation method and application thereof

    CN113025165A

  • Universal thick-film epoxy heavy-duty paint and preparation method thereof

    CN103992727A